Imipridones affect tumor bioenergetics and promote cell lineage differentiation in diffuse midline gliomas. Issue 9 (14th February 2022) - Przystal, Justyna M; Cianciolo Cosentino, Chiara; Yadavilli, Sridevi; Zhang, Jie; Laternser, Sandra; Bonner, Erin R; Prasad, Rachna; Dawood, Adam A; Lobeto, Nina; Chin Chong, Wai; Biery, Matt C; Myers, Carrie; et al.
Abstract: Background: Pediatric diffuse midline gliomas (DMGs) are incurable childhood cancers. The imipridone ONC201 has shown early clinical efficacy in a subset of DMGs. However, the anticancer mechanisms of ONC201 and its derivative ONC206 have not been fully described in DMGs. Methods: DMG models including primary human in vitro ( n = 18) and in vivo (murine and zebrafish) models, and patient ( n = 20) frozen and FFPE specimens were used. Drug-target engagement was evaluated using in silico ChemPLP and in vitro thermal shift assay. Drug toxicity and neurotoxicity were assessed in zebrafish models. Seahorse XF Cell Mito Stress Test, MitoSOX and TMRM assays, and electron microscopy imaging were used to assess metabolic signatures. Cell lineage differentiation and drug-altered pathways were defined using bulk and single-cell RNA-seq. Results: ONC201 and ONC206 reduce viability of DMG cells in nM concentrations and extend survival of DMG PDX models (ONC201: 117 days, P = .01; ONC206: 113 days, P = .001). ONC206 is 10X more potent than ONC201 in vitro and combination treatment was the most efficacious at prolonging survival in vivo (125 days, P = .02). Thermal shift assay confirmed that both drugs bind to ClpP, with ONC206 exhibiting a higher binding affinity as assessed by in silico ChemPLP. ClpP activation by both drugs results in impaired tumor cell metabolism, mitochondrial damage, ROS production, activation of integrative stress response (ISR), and apoptosis in vitro and in vivo. Strikingly, imipridone treatment triggered a lineage shift from a proliferative, oligodendrocyte precursor-like state to a mature, astrocyte-like state. Conclusion: Targeting mitochondrial metabolism and ISR activation effectively impairs DMG tumorigenicity. These results supported the initiation of two pediatric clinical trials (NCT05009992, NCT04732065).